Reduced fixed dose tocilizumab 400 mg IV compared to weight-based dosing in critically ill patients with COVID-19: A before-after cohort study - Sophie Stukas; George Goshua; Angus Kinkade; Rebecca Grey; Gregory Mah; Catherine M. Biggs; Shahin Jamal; Sonny Thiara; Tim T.Y. Lau; Jolanta Piszczek; Nilu Partovi; David D Sweet; et al. (The Lancet Regional Health. Americas, 2022)
Summary: Background: Interleukin-6 inhibitors reduce mortality in severe COVID-19. British Columbia began using tocilizumab 8 mg/kg (maximum 800 mg) in January 2021 in critically ill patients with COVID-19, but due to drug shortages, decreased dosing to 400 mg IV fixed dose in April 2021. The aims of this study were twofold: to compare physiological responses and clinical outcomes of these two strategies, and examine the cost-effectiveness of treating all patients with 400 mg versus half the patients with 8 mg/kg and the other half without tocilizumab. Methods: This was a single-centre, before-after cohort study of critically ill COVID-19 patients treated with tocilizumab, and a control cohort treated with dexamethasone only. Physiological responses and clinical outcomes were compared between patients receiving both doses of tocilizumab and those receiving dexamethasone only. We built a decision tree model to examine cost-effectiveness. Findings: 152 patients were included; 40 received tocilizumab 8 mg/kg, 59 received 400 mg and 53 received dexamethasone only. Median CRP fell from 103 mg/L to 5.2 mg/L, 96 mg/L to 6.8 mg/L and from 81.3 mg/L to 48 mg/L in the 8 mg/kg, 400 mg tocilizumab, and dexamethasone only groups, respectively. 28-day mortality was 5% (n=2) vs 8% (n=5) vs 13% (n=7), with no significant difference in all pair-wise comparison. At an assumed willingness-to-pay threshold of $50,000 Canadian per life-year, utilizing 400 mg for all patients rather than 8 mg/kg for half the patients is cost-effective in 51.6% of 10,000 Monte Carlo simulations. Interpretation: Both doses of tocilizumab demonstrated comparable reduction of inflammation with similar 28-day mortality. Without consideration of equity, the net monetary benefits of providing 400 mg tocilizumab to all patients are comparable to 8 mg/kg to half the patients. In the context of ongoing drug shortages, fixed-dose 400 mg tocilizumab may be a practical, feasible and economical option. Funding: This work was supported by a gift donation from Hsu & Taylor Family to the VGH Foundation, and the Yale Bernard G. Forget Scholarship.